The wheat supply chain in Ethiopia: Patterns, trends, and policy options - Minot, Nicholas; Warner, James; Lemma, Solomon; Kasa, Leulsegged; Abate, Gashaw T.; Rashid, Shahidur (International Food Policy Research Institute, 2015)
The report is one of a series of commodity studies to be carried out by the International Food Policy Research Institute at the request of the Ethiopian Agricultural Transformation Agency (ATA). The general goal of these studies is to provide a comprehensive description of the commodity marketing channel from production to consumption to assist the ATA in its work of raising crop productivity and improving market efficiency.